The Influence of Financial Literacy, E-Money, and Hedonism Lifestyle on the Financial Management of Management Students 2019-2021 UBP Karawang - dayanti, dhea; Mulyadi, Dedi; Pertiwi H. S., Santi; Uus Mohammad Darul Fadli (Research in Management of Technology and Business, 2024)
The aim of this study is to find out how the influence of financial literacy, electronic money, and lifestyle hedonism impacts management students at Buana Perjuangan University Karawang in 2019–2021. The number of samples collected was one hundred people from the surveyed population. We collected data in this research through observation, using a Google Forms-provided questionnaire. This research was carried out quantitatively by conducting path analysis and using the SPSS24 application program. The results of this study show that, although there is a lower and positive correlation between the financial literacy variable and the hedonistic lifestyle, there is a fairly strong and positive correlation between the e-money variable and the hedonistic lifestyle. Simultaneously, all variables that depend on financial literacy, including e-money and a hedonistic lifestyle, have a positive and significant impact on financial management. However, partially, e-money and a hedonistic lifestyle have no influence on financial management.